PENERAPAN MODEL ROLE PLAYING DALAM PEMBELAJARAN TEKS NEGOSIASI KELAS X SMK NASYRUL ULUM GEGESIK TAHUN PELAJARAN 2024/2025 - Kusaeni, Novia; Maskur Subaweh, Ahmad; Sholeh, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Computational thinking skills are skills needed to solve various problems that arise in everyday life. Based on the international study of the Programme for Student (PISA), Indonesian students have low thinking and reasoning skills. Therefore, this study aims to develop a game-based learning media (product) called "Swapmaster", to help develop students' computational thinking skills. The method used in this study is the Research and Development (R&D) method, with the stages of the Borg and Gall model that have been adjusted to the needs of the study. These stages include 1) Research and Data Collection, 2) Planning, 3) Making a draft version of the product, 4) Initial validation test 5) Implementation of analysis (operational field test). The results of the study showed that the application of the Swapmaster learning media that had been validated by experts was able to improve students' computational thinking skills and was included in the "Good" criteria.